(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
This research was conducted with the aim of identifying the role and effect of localized root zone bacteria (R. meliloti, B. lupine, B. subtilus, Azotobacter sp.) In the soil (Rhizosphere) on some pesticide residues locally available in Wadi Al-Shati area, Libya, where residues of these pesticides accumulate in cultivated plants and often reach the following seasons. The pesticides degradation results showed that (R. meliloti) bacteria had no clear role in Chlorpyrifos and Linron breakdown while it worked to destroy significant concentrations of the pesticide after 12 hours with the microbes continuing to grow up to 24 hours, and the breakdown of the Glyphosate increased by the increasing of the dose Used. The results also showed that Linron has the ability to resist the biological decomposition of B. lupine, and the bacteria have no active role in Chlorpyrifos degradation, but it breaks down Glyphosate during 12 hours of exposure, and the microbe continued to grow until 24 hours, then the activation of the pesticide occurred and it became more resistant to biodegradation, and the bacteria had the ability to breakdown the pesticide. While (B. subtilus) bacteria has no role in degradation of Chlorpyrifos and Glyphosite, the microbe contributed to breaking Linron within 12 hours, then activation of the pesticide occurred over time, the longer the exposure period, the greater the resistance of the pesticide to decomposition and that the bacteria had no role in cracking Sencor during the first hours of exposure, but after 24 hours of exposure, the pesticide began to collapse. Azotobacter had no effect on Chlorpyrifos during the first hours of exposure, increased with the increased exposure period, the duration of the pesticide’s survival, and the resistance to Linron decomposition increased with increasing concentrations used. The Glyphosate collapse did not occur within the first 12 hours of exposure, and then the destruction of the pesticide occurred after 12-24 hours, and then the pesticide returned to its activity within 72 hours. It is concluded that Azotobacter was more effective on the pesticides used, followed by the bacteria (B. lupini) and the bacteria (B. subtilus) and finally (R. meliloti).